Terahertz near-field microscopy of ductal carcinoma in situ (DCIS) of the breast. (22nd October 2020) - Okada, Kosuke; Serita, Kazunori; Cassar, Quentin; Murakami, Hironaru; MacGrogan, Gaëtan; Guillet, Jean-Paul; Mounaix, Patrick; Tonouchi, Masayoshi
Abstract: Imaging with terahertz (THz) waves has been expected as a non-invasive/non-staining visualization tool for breast cancer margins during surgeries. Breast cancer is a generic name for a heterogeneous lesion comprising invasive adenocarcinoma, in situ adenocarcinoma, most frequently in the form of ductal carcinoma in situ (DCIS) and benign tissues. Until now, THz imaging has focused on invasive adenocarcinoma; however, THz analysis of DCIS has hardly been performed. One of the reasons is that the size of an individual DCIS lesion, ranging from 50 to 500 µ m, is typically much smaller than that of an invasive carcinoma. This makes it difficult to identify these lesions by THz imaging, which has only a diffraction-limited spatial resolution of several millimeters. To overcome this drawback, we have developed a scanning point terahertz source (SPoTS) microscope with a resolution of 20 µ m, in which a near-infrared-pump-laser-induced two-dimensionally-scannable point THz source ( φ THz ≍ φ Pump ) generated in a GaAs crystal contacts a sample. In this study, utilizing this state-of-the-art microscope, we mainly performed THz near-field transmission imaging of a paraffin-embedded human breast cancer sample containing invasive carcinoma and DCIS, as a preliminary study. Consequently, for the first time, we succeeded in clearly visualizing a DCIS lesion of ∼ φ 500 µ m in the THz images. It was also found that the THz attenuation by DCIS was higher than that by invasive ductal carcinoma. Furthermore, also in a reflection-mode measurement, we successfully obtained a similar outcome to the above transmission-mode one. These results can be caused by the interaction between the THz waves and the cellular density, indicating that SPoTS microscopy may be suitable for DCIS diagnosis.